Función diafragmática y neumonía intrahospitalaria en pacientes con hemiplejía por desorden vásculo cerebral isquémico - Tito Mallqui, Bryan Dalmacio (2017)
The Vascular Cerebral Disorder (VDC) or stroke is a neurological pathology whose most common motor sequel is the hemiplegia that affects mainly the posture and muscle tone, including the respiratory muscles. It’s been proven that the diaphragmatic function is altered in respiratory and contractile capacities. This decreases the mucociliary cleanse and increases the risk of aspiration pneumonia. In this paper we review the current knowledge on nosocomial pneumonia and diaphragmatic function in post stroke patient.